Komunikasi Humas Bank Indonesia mengenai QRIS melalui Media Sosial Instagram di Kota Ternate - Nurul Sheila Abdullah; Yenni Yuniati (Bandung Conference Series: Public Relations, 2024)
Abstract. Instagram social media as a communication medium for conveying messages and information in the current era of digitalization is very helpful and makes it easier for every person or institution and organization to carry out the communication process. Through the advantages of social media, every communication process can run and various types of messages can be conveyed instantly without the barriers of time and space. One of them is delivering messages regarding the QRIS service introduced by Bank Indonesia via Instagram social media. As a network of Bank Indonesia's financial and monetary headquarters, the North Maluku Province Representative Office contributes by participating in compiling and publishing a digital money service or Qris. Of the many residents in Ternate City, there are still few people who are aware of technology, especially technology in the field of non-cash services (QRIS). This research uses a qualitative research method with a descriptive case study approach. The researcher considers it important to conduct scientific research in the form of a thesis "Bank Indonesia Public Relations Communication Regarding Qris Via Instagram Social Media in Ternate City (Case Study of Bank Indonesia Public Relations in North Maluku Province)". Until finally in this research it was found that the way Bank Indonesia North Maluku introduced Qris to the public was by holding the Serumbi festival, the Mantan Festival, socializing about Qris, making short films, making posts, Instagram stories and reels. Abstrak. Media sosial Instagram sebagai salah satu media komunikasi dalam menyampaikan sebuah pesan dan informasi diera serba digitalisasi seperti sekarang ini sangatlah membantu dan mempermudah setiap orang atupun suatu lembaga dan organisasi dalam melakukan proses komunikasi. Melalui kelebihan media sosial setiap proses komunikasi dapat berjalan dan beragam jenis pesan dapat tersampaikan secara instan tanpa peghalang ruang dan waktu. Salah satunya adalah penyampaian pesan mengenai layanan QRIS yang di perkenalkan oleh Bank Indonesia melalui media sosial Instagram. Sebagai jaringan kantor pusat keuangan dan moneter Bank Indonesia, Kantor Perwakilan Provinsi Maluku Utara berkontribusi dengan ikut serta menyusun dan menerbitkan suatu layanan uang digital atau Qris. Dari sekian banyak penduduk di Kota Ternate masih tercatat minim masyarakat yang sadar akan teknologi khususnya teknologi di bidang layanan non tunai (QRIS). Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus deskriptif. Peneliti menganggap penting untuk melakukan penelitian ilmiah dalam bentuk skripsi “Komunikasi Humas Bank Indonesia Mengenai Qris Melalui Media Sosial Instagram di Kota Ternate (Studi Kasus Pada Humas Bank Indonesia Provinsi Maluku Utara)”. Hingga akhirnya dalam penelitian ini ditemukan bahwa cara Bank Indonesia Maluku Utara memperkenalkan Qris kepada masyarakat yaitu dengan membuat festival Serumbi, Festival Mantan, Sosialisasi mengenai Qris, membuat film pendek, membuat postingan, instagram stories, dan reels.